(untitled) (Research, Society and Development, 2021)
Solid waste is one of the biggest polluters of the environment in these days, causing serious environmental, economic and social problems. Working on this problem is necessary, and it is essential to change the attitudes and mentality of individuals. In this sense, this work aimed to build and analyze pedagogical actions based on the problem of solid waste in a beach, which were articulated with Chemistry Education. The study was carried out with a group of 9 students from the Technical Course on Environment in the region of Baixo Tocantins in the state of Pará. The methodology was based on a qualitative approach within the technique of case study and content analysis. The research was divided into 4 stages: bibliographic research in scientific repositories; field activity; elaboration, validation and application of a questionnaire; finally, the thematic workshop “Transforming garbage into art”. The results showed that the discussion of environmental issues combined with the teaching of Chemistry and Art provides a meaningful teaching, developing a critical and reflective sense about problematized situations, however, actions such as those proposed in this work should not be seen as direct responses to environmental issues or difficulties in the teaching-learning process of Chemistry.